Antimicrobial Susceptibilities of Escherichia coli Isolates from Food Animals and Wildlife Animals in Sarawak, East Malaysia. - K, Apun; YL, Chong; MT, Abdullah; V, Micky (Researchgate Publisher, 2008)
A total of 133 E. coli strains isolated from different food animals and wildlife sources in Sarawak, Malaysia were screened to determine their antibiotic resistance pattern using the disk diffusion methods.